Important concepts in immunizations - Verne Martin, Eduardo (2007)
The present article develops basic concepts on immunizations, taking into account fundamental aspects of immunity, pertinent deﬁnitions, the importance of an intact cold chain, techniques for vaccine administration, as well as events associated with vaccines and different vaccination schemes. It also includes a vaccination schedule, which might be considered the present ideal schedule. Vaccines are humanitys best medical achievement, because they prevent illnesses before they happen. Humanity, speciﬁcally thousands of researchers around the world, constantly develops efforts to produce new vaccines against several diseases which are major threats to human health. Vaccines exist in different phases of study or are already available for tuberculosis, malaria, dengue, meningococcus, meticillin resistant staphylococcus aureus, group B streptococcus, Helicobacter pylori, avian inﬂuenza, respiratory sincycial virus, rabies, typhoid fever, paratyphic diseases, E. coli, adenovirus, HIV, rheumatoid arthritis; vaccines that can be eaten as food and many other advances have recently been developed; it may be emphasized that the future of medicine is evolving towards prevention.